Digital Financial Literacy and Financial Well-Being - Youngjoo Choung; Swarn Chatterjee; Tae-Young Pak (Finance Research Letters, 2023)
Digital financial literacy is an emerging concept that emphasizes necessary knowledge and skills to carry out financial transactions on digital platforms. In this study, we aim to examine the link between digital financial literacy and financial well-being among Korean adults. Using online survey data, this study shows that digital financial literacy is associated with financial well-being, and this association is largely due to financial knowledge and the ability to protect against digital fraud. Digital financial literacy carried larger marginal effects on financial well-being compared to financial knowledge, and demonstrated significant effects across sociodemographic groups. Implications for financial education were discussed.
Keywords: D14; G50; G53; I31; O53; 330; digital finance; financial literacy; digital literacy; financial inclusion; financial well-being; South Korea